PENGUKURAN DAN ANALISA SINYAL RF PADA PENERIMA SELULER DI AREA SURABAYA (RF SIGNAL MEASUREMENT AND ANALYSIS ON CELLULAR RECEIVER IN SURABAYA) - Moh Oky Sadam Basri; Achmad Mauludiyanto (SENTIA 2016, 2016)
In 2006, 3G tech was first introduced to public. It become new technology that has been used by a lot of people because this technology gives them fast access and better quality. A lot of new technolocy based on 3G occur, from 4G until the latest technology called 5G. Continous maintain and surveilance are needed to keep cellular network quality good. A lot of nework operator and service provider still use drive test to measure signal quality on certain area. That way of planning sure take alot of time and resources. In this final project, writer do cellular signal measuring on 3G technology in dense urban, urban, and sub urban area. The writer also do some link budget calculating and signal quality modelling. In this modelling, writer use ARIMA method as a way. Cellular signal quality on Surabaya have RSL value beetwen -50 dBm and -80 dBm. And based on parameters in the modelling test, writer choose ARIMA (2,0,1) as a way to predict and calculate cellular signal quality in those area. This ARIMA (2,0,1) has accuracy above 90%.